Potato Farming Management in Sloping Upland - Arifin, Zainal; Anggraeni, Listy; Latifah, Evy (Current Topics in Agricultural Sciences Vol. 8, 2022)
This study aimed to obtain a potato farming conservation technology package that can increase the productivity and income of potato farming and reduce the soil erosion rate. With the soil erosion problem in potato cultivation especially on sloping land, there is some cultivation technique to manage that problem which can also increase the potato yield and decrease the loss of plant nutrients. The comparison of farmer patterns, improved patterns, and the integrated patterns will provide a view of the best pattern of potato cultivation. Each pattern gives an overview of different plant performance, pest and disease attack, potato yield, and reduction of soil erosion that has been seen from soil structure and nutrients in soil and plants. Besides that, the integrated pattern is a very suitable pattern to use to reduce erosion and deal with sloping land farming problems.